Arterial stiffness and endothelial function in obstructive sleep apnoea: the effect of Continuous Positive Airway Pressure (CPAP) therapy - Jones, Anne (The University of Edinburgh, 2016)
Introduction: Obstructive sleep apnoea (OSA) is common and is caused by repetitive obstruction of the upper airway during sleep. OSA is associated with increased cardiovascular morbidity and mortality and is an independent risk factor for hypertension. The immediate physiological effects of OSA include intermittent hypoxia, repeated arousal from sleep and intra-thoracic pressure swings. The resulting activation of the sympathetic nervous system, systemic inflammation and oxidative stress may result in increased arterial stiffness and endothelial dysfunction, potentially explaining any causal link between OSA and cardiovascular disease (CVD). Continuous positive airway pressure (CPAP) therapy improves excessive daytime sleepiness (EDS) and in non-randomised studies, reduces cardiovascular mortality. Prior to starting this study, there was a limited amount of evidence suggesting that CPAP therapy improved arterial stiffness and endothelial function, but the effects in subjects without pre-existing CVD were unclear. Aims: i) to determine whether CPAP therapy has an effect upon measures of arterial stiffness and endothelial function in patients with OSA, in the absence of known CVD. ii) To compare arterial stiffness and endothelial function in a subset of patients with OSAHS (defined as OSA and EDS), with a group of well-matched control subjects. Methods: Fifty three patients with OSA, defined as an apnoea/hypopnoea index of ≥15, and without known CVD, entered a double-blind placebo-controlled crossover trial of 12 weeks CPAP therapy, of whom forty three completed the study protocol. Sham CPAP was used in the placebo arm of the study and vascular assessments were made at baseline and after each arm of the study. Arterial stiffness was determined by measuring aortic distensibility using cardiovascular magnetic resonance imaging and by measuring the augmentation index (AIx) and aortic pulse wave velocity (PWV) by applanation tonometry. Endothelial function was assessed non-invasively by measuring vascular reactivity after administration of salbutamol and glyceryl trinitrate. In a subset of twenty patients with OSAHS, arterial stiffness and endothelial function at baseline were compared to readings obtained from healthy control subjects, matched on a one-to-one basis for age, sex and BMI. Results: Patients with OSAHS (n=20) had increased arterial stiffness [AIx 19.3(10.9) vs. 12.6(10.2) %; p=0.017] and impaired endothelial function, measured as the change in AIx following salbutamol [-4.3(3.2) vs. -8.0(4.9) %; p=0.02] compared to controls. Twelve weeks of CPAP therapy had no significant effect upon any measure of arterial stiffness or endothelial function in patients with OSA (n=43). A trend towards a reduction in AIx following CPAP therapy was seen, but this was non-significant. There was a reduction in systolic blood pressure following CPAP therapy [126(12) vs. 129(14) mmHg]. Sub group analysis showed CPAP to have no effect on arterial stiffness or endothelial function in patients with EDS or in patients using CPAP for ≥4 hours per night. Conclusions: This study demonstrates that even in the absence of known CVD, patients with OSAHS have evidence of increased arterial stiffness and impaired endothelial function. However, in patients with OSA, free from CVD, CPAP therapy did not lead to an improvement in any measure of arterial stiffness or endothelial function after 12 weeks.
Keywords: obstructive sleep apnoea/hypopnoea syndrome; cardiovascular disease; arterial stiffness; endothelial dysfunction; continuous positive airway pressure; CPAP